Analysis of human capital lecturer factors in the process of achieving the vision of higher education - Uus Mohammad Fadli; Citra Savitri; Budi Rismayadi (IJHCM (International Journal of Human Capital Management), 2022)
ABSTRACT The purpose of this study is to identify the factors that play a role in building Human Resources for Higher Education Lecturers and the process of their formation. This study uses a quantitative approach, collecting data using a questionnaire to 166 lecturers from higher education in Karawang Regency, West Java. Data analysis used factor analysis and dendogram analysis. The results of factor analysis showed that all indicators were analyzed from the basic components, moderators, supporters and outputs of Human Resources for Higher Education Lecturers. The results of the dendogram analysis inform that the process of forming the Human Capital for Higher Education Lecturers begins with educational activities and faculty skills. This research is still in the study of the identification of intellectual capital which is explained to individual university lecturers with a small sample area, so it is still necessary to develop the intellectual capital relationship of lecturers with other variables that reflect the university's business processes. The results of this study greatly contribute to explaining the potential of human capital as an intangible asset of higher education and the process of its formation, so that universities can understand how to develop lecturers' human capital so that its potential can be used for the development of higher education as a whole.